Continuity Amidst Change: Village Organization and Fishing Subsistence at the Dionisio Point Locality in Coastal Southern British Columbia. (2nd January 2018) - Hopt, Justin; Grier, Colin
ABSTRACT: Shifts over time in faunal representation in Northwest Coast archaeological sites have been viewed as reflecting changes in economic organization and social complexity. We use fish faunal data from the Parry Lagoon Midden (site DgRv-006) in the Salish Sea region of coastal southwestern British Columbia, Canada, to evaluate the relationship between change in subsistence strategies and community organization. We describe and compare fish assemblages recovered from a shell midden generated by habitation at two sequentially occupied village sites. The lower midden layers include faunal remains derived from the Marpole Period plankhouse village occupation at site DgRv-003 (1500 to 1300 cal BP), while the upper layers were generated during the occupation of a Late Period plankhouse within site DgRv-006 (1000 to 600 cal BP). We compare the two faunal records to ascertain if subsistence re-organization accompanied the social change associated with abandonment and later re-establishment of a village in the Dionisio Point Locality. Results indicate continuity of a diverse fishing economy for the two occupations, and therefore across the Marpole to Late Period transition. This study adds to the recent trend in Northwest Coast archaeology to reconsider the long-standing view that social and subsistence change necessarily occurred in tandem.